2013
DOI: 10.3109/10799893.2013.865745
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of rat neonatal Fc receptor in the principal organs of neonatal and pubertal rats

Abstract: The neonatal Fc receptor (FcRn) mediates the transfer of IgG and albumin, also protects them from catabolism. This study characterized the expression of FcRn in different organs of neonatal and pubertal rats by reverse transcription-PCR (RT-PCR) and immunohistochemistry, demonstrates that FcRn is expressed in liver, kidney, intestine, heart, lung, spleen, skin and skeletal muscles at varying levels post-gestation from d 1 to d 63. This finding is contrary to previous studies claiming that FcRn is undetectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…FcRn has more recently been shown to express in a variety of mammalian species 12 . Meanwhile, several studies have reported the distribution, function, and regulation of human and rodent FcRn expression 9,24,29,30 . Our study demonstrated that pFcRn mediated bidirectional IgG transport across polarized IPEC-J2 cells that potentially provide the mucosal protection 31 .…”
Section: Discussionmentioning
confidence: 99%
“…FcRn has more recently been shown to express in a variety of mammalian species 12 . Meanwhile, several studies have reported the distribution, function, and regulation of human and rodent FcRn expression 9,24,29,30 . Our study demonstrated that pFcRn mediated bidirectional IgG transport across polarized IPEC-J2 cells that potentially provide the mucosal protection 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of IgG and albumin loss through the biliary system. McCarthy et al, 2000;Pike et al, 2013;Simister et al, 1996;Tian et al, 2014;Tzaban et al, 2009) Breast Transfer of passive immunity and tolerance induction. Albumin transport.…”
Section: Professional Apcsmentioning
confidence: 94%
“…The availability of FcRn for intracellular salvage is a key determinant of plasma half‐life. Some preliminary data may suggest lower FcRn concentrations in children, though no definitive argument can yet be made . Three studies have examined FcRn expression in neonatal subjects relative to adults .…”
Section: Methodsmentioning
confidence: 99%
“…Some preliminary data may suggest lower FcRn concentrations in children, though no definitive argument can yet be made . Three studies have examined FcRn expression in neonatal subjects relative to adults . In rats, reverse transcriptase polymerase chain reaction revealed a general trend across all organs of low FcRn mRNA expression at birth relative to adults, though the intestine may be an exception .…”
Section: Methodsmentioning
confidence: 99%